Perancangan dan Pemanfaatan Gambar Naratif dalam Pengajaran Hiwar bagi Pembelajar Dewasa Tingkat Pemula di Lembaga Bahasa dan Ilmu Al-Qur’an Jakarta - Tahmid, Ryan Wildani; Mahyudin, Erta; Royani, Ahmad (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
This study aims to develop an instructional medium in the form of narrative images to support the teaching of hiwar (Arabic conversation) for adult beginners at the Institute of Language and Qur’anic Sciences in Jakarta. The background of this research is the learners’ low comprehension of hiwar in textbooks, which is partly due to the poor quality of illustrations that do not effectively support learning. This research employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) by Robert Maribe Branch. Data were collected through observation, interviews, questionnaires, and documentation involving 63 students. The developed product consists of contextual narrative images designed using Canva, featuring characters and settings relevant to help learners understand hiwar more imaginatively and interactively. Validation results indicate that the media is highly feasible, with a score of 93% from media experts, 100% from teachers, and 87% from student responses, all categorized as "excellent." These findings demonstrate that narrative image-based media is effective in enhancing learners' comprehension and engagement in learning Arabic hiwar.